Putative Plastic Degrading Communities Within New Zealand’s Geothermal Environments - Pavlov, N; Wallbank, JA; Hermans, SM; Kingsbury, JM; Pantos, O; Lear, G (Elsevier BV, 2025)
The molecular mobility of plastic polymers increases above their glass transition temperature (i.e. above 70°C for polyethylene terephthalate, PET), making them more susceptible to microbial biodegradation. Microorganisms that can survive in hot environments and produce thermostable enzymes may play crucial roles in plastic biodegradation. However, their presence in geothermal areas remains understudied. We conducted 16S rRNA gene sequencing of microbial consortia within geothermal springs at Kuirau Park, Rotorua, Aotearoa-New Zealand, to examine the distributions of putative plastic-degrading taxa. We selected 35 sites with varying pH (4-10) and temperature (20-80°C) conditions. The most abundant putative plastic-degrading taxa belonged to the genera Flavobacterium, Pseudomonas, Sphingomonas and Rheinheimera, which were present in 24 out of the 35 sites examined. We found no clear spatial patterns in the distribution of putative plastic degrading taxa but identified greater relative taxonomic richness within sites with moderate thermophilic conditions (30-40°C). Among the putative degraders identified, only Sphingomonas, Acidovorax, Rhodoferax and Lepthothrix showed a strong Spearman’s rank correlation with studied physiochemical factors, with temperature being more influential than pH on their relative abundances. We confirmed the presence of genes associated with the metabolism of aromatic compounds and various plastic polymers, including PCL, PLA, PU, PET, PES, PVA, and LLDPE, through shotgun metagenomic sequencing of samples with relatively high concentrations of plastic-degrading taxa. Our study confirms a wide presence and distribution of putative plastic-degrading microorganisms and genes in geothermal environments. It highlights the potential of geothermal springs for future research into plastic bioremediation.
Keywords: 3107 Microbiology; 31 Biological Sciences; 41 Environmental Sciences; 14 Life Below Water; Thermophiles; Microbial ecology; Plastic biodegradation; Plastic; DB16S rRNA gene; Shotgun metagenomics